Source and performance of waste-derived porous carbon material as supercapacitor: Biomass, sludge and plastic waste as precursors - Feng, Jinxi; Zhu, Qi; Le, Qingguo; Zhu, Wenlei; Song, Bing; Zhang, Zehui; Lam, Jason Chun-Ho (Renewable & sustainable energy reviews, 2025)
The development of clean and affordable energy storage systems is crucial due to the depletion of fossil fuels and the escalation of environmental concerns. Carbon-rich solid wastes have garnered significant attention as precursors for supercapacitor electrode fabrication because of their abundance, low cost, diverse sources, and sustainable nature. The valorization of solid organic waste aligns with sustainable development goals (SDGs 7, 9, 11–13, 15, and 17), contributing to the global mission of sustainable development. This review addresses recent studies on carbon electrode materials for supercapacitors, focusing on three major types of organic solid wastes––biomass, sludge, and plastics––as precursors for producing porous electrode materials. The capacitance properties, energy storage performance, and activation processes of these materials are summarized, discussed, and analyzed based on extensive examples sourced from biomass, sludge, and plastic wastes. Although these waste streams differ inherently in composition and availability, all can serve as viable sources for producing porous materials. Interestingly, reported data indicate that the electrochemical performance of these carbon materials is not strongly dependent on their specific surface areas or feedstock origin, even when prepared using similar processes and electrolytes. Although some wastes contain self-dopants theoretically predicted to enhance electrochemical performance, their carbon materials do not always exhibit superior performance compared to others. Given the considerable economic and environmental benefits of waste-derived carbon materials, continuous research in this area remains essential. We hope this overview will promote the upcycling of organic solid waste for energy storage material production, thus contributing positively to the growing demand for renewable energy storage. [Display omitted] •Biomass-, sludge-, and plastic-derived porous carbon for supercapacitors were deeply reviewed.•Waste-based carbon materials evaluated as promising candidates for electrode materials.•Investigation of the relationship between surface area and electric capacitance.•Future research should focus on emerging waste sources, real-time characterization, and machine learning adaptation.